Analisis Model Pembiayaan Pendidikan Mandiri Berbasis Infaq dan Implikasinya Terhadap Mutu Pembelajaran - H Soro, Suharyanto; Muhammad Jalil, Dani; Khoirudin, Asmi (UIN Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the infaq-based independent education financing model and its implications for learning quality at MTs Al-Fatah, Bandung Regency. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and document studies. The research subjects consisted of school principals, treasurers, teachers, school committees, parents, and students. The results showed that MTs Al-Fatah has implemented an infaq-based financing model since 2022 with a flat rate of IDR 25,000 per month per student. Fund allocation consists of 40% for operational needs, 40% for uncovered honorarium from BOS funds, and 20% for infrastructure maintenance. This financing model has a positive impact on learning quality as evidenced by an increase in student-book ratio from 0 in 2020 to 1 per subject in 2024, improvement in teacher qualifications from 70% S1 in 2020 to 90% S1 in 2024, and student satisfaction reaching 95/100. The collectibility rate reaches 90% with high parent satisfaction. This study concludes that infaq-based financing models can be an alternative solution for madrasah financial independence while maintaining learning quality and community trust.